Sperm epigenetics in the study of male fertility, offspring health, and potential clinical applications. (4th March 2017) - Jenkins, Timothy G.; Aston, Kenneth I.; James, Emma R.; Carrell, Douglas T.
ABSTRACT: The mammalian sperm contains a highly unique and specialized epigenetic landscape that offers a great degree of interesting research opportunities. One key discriminating feature of the mature sperm epigenome is that it, in theory, represents both remnant marks used throughout spermatogenesis to generate sperm cells competent to perform their function, but also marks that appear to be useful beyond fertilization. Key questions must be asked about the utility of these marks and the multiple purposes that may be served. It is this unique epigenetic landscape that has driven some labs to begin to study the links between aberrant sperm epigenetic patterns and various forms of infertility, from idiopathic to alterations in sperm motility, morphology, and viability and fertilization capacity. Because of the unique nature of the sperm epigenome and the patterns found in mature sperm that appear to reflect perturbations in spermatogenesis that may ultimately have effect on pregnancy outcomes, some researchers believe that these marks may provide predictive insight that can be exploited. Indeed, there is emerging data suggesting that the predictive power of DNA methylation and RNA signatures in sperm likely exceeds that which can be found with traditional assessments of male infertility. This review will focus on the utilization of the sperm epigenome as a potential diagnostic tool in the context of male infertility, as well as the potential difficulties associated with such an approach.